ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL GURU AINI KARYA ANDREA HIRATA - Ahmad Izza Muttaqin; Riza Faishol; Diva Fidya Fitri Cahayaningrum (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
In all forms of limitations in the midst of this pandemic, the planting of character education values does not have to go through formal educational institutions such as schools. It can be easily internalized through reading books that contain many values of character education. The novel Guru Aini by Andrea Hirata published in early 2020 is a literary work closely related to character values. Methodologically, this literature research belongs to a qualitative type of research. The primary data source or primary data source in this study is Guru Aini's novel by Andrea Hirata which has been published by Bentang Pustaka in early 2020 while secondary data is obtained from other literacy such as journals or previous thesis with the same context. The data collection procedure is carried out with text analysis, discourse analysis and field notes. In this study the method of analysis used is content analysis. The commonly used technique is symbol coding. The results showed that Guru Aini's novel by Andrea Hirata contains the values of Indonesian character education based on 18 character values and developed by Diknas and has relevance to the values of character education in Indonesia.